Exploring a linguistic intergroup bias on communication of compound-word names and acronyms among political parties - Chisango, Tadios; Mayekiso, Thokozile (Oxford University Press, 2019)
According to the linguistic intergroup bias (LIB), positive actions of ingroup members are described with more abstract predicates than those of outgroup members, whereas negative actions of ingroup members are described with more concrete predicates than those of outgroup members. The researchers extrapolated the LIB to compound-word names (for example African National Congress) and their acronymic equivalents (for example A.N.C). They theorized that compound-word names are positive abstract terms, thus, suiting description of the ingroup’s positive identity. Besides, their concrete equivalents acronyms can be easily ascribed a negative meaning and, thus, would be suitable for outgroups. Using content and discourse analysis on a sample of nine African political parties, they investigated the hypothesis that people mention a compound-word name of an ingroup more frequently than of outgroups. Results indicated that people use compound-word names more frequently than outgroups. They explained the effect as a form of a linguistic intergroup bias.